Biofunctional Understanding and Judgment of Size - Jin, Zheng; Lee, Yang; Yuan, Zheng (Frontiers in Psychology, 2016)
Research has shown that the meaningfulness of the material increases judged size, whereas symmetry decreases size judgments. These findings have been interpreted in terms of information processing, with a greater quantity of information leading to a judgment of larger size. An alternative view based on biofunctional understanding theory emphasizes the quality of affordance-triggered biological activity as reported and observed in attitudes toward playing sports, effortless understanding, knowledge-in-action, meditative wisdom, and body-mind cycle of adaptation. This alternative implies that affordance biofunctional activity is naturally size-diminishinging as it moves toward coherence and size-expanding as it moves away from coherence influencing judgments of size accordingly. Here we tested this hypothesis in the realm of sensorimotor integration. Our first experiment showed that phonologically unpronounced or symmetric symbols elicit smaller size judgments than phonologically pronounced and asymmetric symbols. Next, we manipulated the quantity of meaning with the affordance (possibilities for biofunctional activity) orthogonally in a second experiment, results indicated that meaning affects size judgments only in the absence of phonological information. We conclude that the biofunctional activity affordance may be responsible for observed differences in size judgment.